Experience of Cefixime Application for the Treatment of Urinary Tract Infection in Children - G.O. Lezhenko; O.Ye. Pashkova; O.I. Rudova; Ye.I. Rubanova (Zaslavsky O.Yu., 2014)
There has been investigated the efficiency of Cefix (cefixim) application as a monotherapy of acute cystitis, acute and chronic pyelonephritis in children. Cefixime was found to be etiologically reasonable, high-performance and safe for the therapy of non-complicated cystitis and pyelonephritis in children.